2018
DOI: 10.1002/cncr.31285
|View full text |Cite
|
Sign up to set email alerts
|

Nine‐year prostate cancer survival differences between aggressive versus conservative therapy in men with advanced and metastatic prostate cancer

Abstract: The authors did not observe a survival advantage with local therapy in addition to standard androgen deprivation therapy for men with metastatic prostate cancer. However, the results of the current study did affirm advantages in the setting of locally advanced disease. Aggressive local therapy in the setting of metastatic disease needs to be studied carefully before clinical adoption. Cancer 2018;124:1921-8. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…These findings appear substantially in contrast to the results of Dall'Era et al In our opinion, the article is flawed with a lack of crucial data, particularly details regarding RT doses, for the interpretation of the results. Rusthoven et al stratified patients into those who received ≥65 Gy and those who received <65 Gy (where the 65‐Gy dose limit was defined as minimum cutoff for therapeutic RT) to evaluate their hypothesis about the potential role of an aggressive local approach to mPCa in accordance with the aforementioned trials showing a survival benefit when RT was added to ADT for locally advanced nonmetastatic prostate cancer …”
contrasting
confidence: 69%
See 1 more Smart Citation
“…These findings appear substantially in contrast to the results of Dall'Era et al In our opinion, the article is flawed with a lack of crucial data, particularly details regarding RT doses, for the interpretation of the results. Rusthoven et al stratified patients into those who received ≥65 Gy and those who received <65 Gy (where the 65‐Gy dose limit was defined as minimum cutoff for therapeutic RT) to evaluate their hypothesis about the potential role of an aggressive local approach to mPCa in accordance with the aforementioned trials showing a survival benefit when RT was added to ADT for locally advanced nonmetastatic prostate cancer …”
contrasting
confidence: 69%
“…We read with particular interest the article written by Dall'Era et al In their study, the authors found no survival benefit for local therapies in addition to standard androgen deprivation therapy (ADT) for men with metastatic prostate cancer (mPCa). Nevertheless, the results of the same study reported advantages for locally advanced disease.…”
mentioning
confidence: 99%
“…We appreciate the comments from Alongi et al regarding our article and agree with many of their excellent points. Notably, patients included in our data set were all treated in 2004, a time when standard computed tomography and technetium‐99 bone scans were used for staging purposes.…”
supporting
confidence: 62%
“…Some retrospective studies had yielded results similar to ours. [ 7 , 9 , 10 , 16 , 17 20 ] For instance, A 9-year follow-up of 275 cT3-4 or N1 and M0 patients diagnosed in 2004 showed that patients received RP had significantly higher CSS than those received EBRT. However, this study didn’t focus on the comparison of RP and EBRT, while the number of samples was small.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study didn’t focus on the comparison of RP and EBRT, while the number of samples was small. [ 10 ] Earlier, a group of researchers followed patients diagnosed with localized PCa from 1992 to 1994 for a median follow-up time of 13.3 years. In their D’Amico high-risk group, the cancer-specific mortality of patients received radiotherapy was 2.3 times higher than those received surgery.…”
Section: Discussionmentioning
confidence: 99%